Differences in anthropometric characteristics and physical fitness based on playing position in elite youth soccer players - Rites, A. A.; da Silva, R. C. F.; de Souza, E. B.; dos Santos, R. P.; Pinto, V. S.; Paulucio, D.; Miranda, H.; Gomes, D. V.; Lattari, E. (The Journal of Strength and Conditioning Research, 2026)
To examine differences in anthropometric characteristics and physical fitness based on playing position in elite youth soccer players, a comparative cross-sectional study was conducted on 160 male players in the U13-14, U15-16, and U17-20 categories. The players were grouped as lateral defender (LD), central defender (CD), midfielder (MF), and attacker. During the first visit, anthropometric assessments, squat jump (SJ), and countermovement jump (CMJ) were conducted. On the second visit, 48 hours later, a 20-meter sprint test and the Yo-Yo intermittent recovery level 1 test were performed. Height, body mass, lean mass, vertical jumps, 20 m sprint, and Vo2max all increased with advancing age (p <= 0.001). A main effect of position (p <= 0.001) showed that CD had higher stature, body mass, and lean mass than players in other positions. In addition, CD exhibited higher values than LD for SJ and CMJ height (p < 0.05). The U17-20 group exhibited greater SJ and CMJ peak power than the U15-16 and U13-14 groups (p <= 0.001 for all comparisons). In addition, CDs outperformed all other positions in SJ peak power and showed higher CMJ peak power than LDs and MFs across all age categories. This study demonstrated that height, body mass, lean mass, vertical jump performance, sprint speed, and Vo2max all increased with advancing age in youth soccer players. Central defender consistently exhibited higher values for these physical characteristics than players in other positions, including LD, particularly in SJ and CMJ performance.